The journal Pengaruh Etika Bisnis Islam Terhadap Keberlanjutan Usaha UMKM Offline dan Online di Kabupaten Bojonegoro - Ahmad Mustafa Lutfi; Akmal Bayu Aji; Anwar Saleh Hasibuan; Arif Al Anang; Moch. Nur Aziz Rifa’i (Journal of Innovative and Creativity, 2026)
This study aims to describe a conceptual model of the influence of Islamic Business Ethics (IBE) on the sustainability of MSMEs in Bojonegoro, comparing the dynamics of offline and online markets. The research uses a Descriptive Qualitative approach based on Systematic Literature Review and Document Analysis (policies and reports). Theoretically, IBE (through Amanah and Siddiq) is the foundation of sustainability through strengthening trust. Its impact mechanisms differ: in Offline, IBE encourages relational loyalty and social justice; in Online, IBE is crucial for mitigating gharar risks and digital reputation. This study recommends developing a specific digital Sharia ethics framework for MSMEs in Bojonegoro to ensure holistic sustainability.